Validación del potencial antioxidante de Citrus aurantium en Tabasco, México - Villarreal_Ibarra , E.C.; Cadenas-González , M.T; Méndez- Morales, F; Bolio-López, G.I; Hernández-Villegas, M.M; Rivera-Torres, N.E; Almenares-López, D.; Rivas Morales, C (Revista de Investigaciones Universidad del Quindío, 2023)
Citrus aurantium L. (Rutaceae), commonly known as bitter orange, has multiple therapeutic potentials. An experimental qualitative study was carried out with the objective of knowing the characteristics of the consumption of C. aurantium (CA) in the Tabasco population. To validate its use, an ethanolic extract (85 %) was prepared from the dry CA leaves and phytochemical screening was performed, with subsequent quantification of the content of total phenols and flavonoids. Subsequently, antioxidant activity was determined by the DPPH assay and acute toxicity with Artemia salina. The most used parts of the plant are the leaves to relieve muscle pain, cold symptoms. In the phytochemical study it was found that the extract contains alkaloids, flavonoids, coumarins, quinones and tannins. In the thin layer chromatography of the hydroalcoholic extract, the presence of naringin was demonstrated. A total phenol content of 69.42 ± 3.47 EAG/g DM and total flavonoids of 14.78 ± 0.28 EQ/g DM were obtained. It contains antioxidant activity of 9240 ± nmol TEAC/gMS and the acute toxicity test showed moderate toxicity. The results show that the 85% ethanolic extract contains phenolic compounds and flavonoids, allowing to sustain the medicinal and pharmacological properties conferred to the plant in the state of Tabasco.Conclusions: this study showed the existence of phenols and flavonoids, the antioxidant activity of hydroalcoholic extracts from C. aurantium leaves and their moderate toxicity against Artemia salina.